The Significance of the Style of Thinking in Scientific Knowledge - Abdullayev Temur Bobir o‘g‘li (Zien Journals, 2023)
This article reveals the significance of the way of thinking in the process of perception and knowledge of the world, together with the philosophical and methodological aspects, in scientific knowledge. Also, in the evolution of thinking, specific aspects of the dialectics of language and consciousness are distinguished.
Keywords: scientific knowledge; empiricism; positivism